Associations of serum lipid traits with DLBCL: a prospective cohort study from the UK Biobank - Luo, QingQing; Cai, ShanShan; Hu, LinHui; Wang, Ya; Yu, Li (Frontiers in Nutrition, 2026)
BackgroundDiffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL), accounting for approximately 30% of all NHL cases. While serum lipids have been associated with various cancers, their relationship with the risk of DLBCL remains largely unexplored.MethodsThis prospective cohort study included 339,172 participants from the UK Biobank. Baseline serum levels of apolipoproteins A and B (ApoA/B), high-and low-density lipoprotein cholesterol (HDL/LDL), total cholesterol (TC), and triglycerides (TG) were measured. The associations between lipid profiles and DLBCL risk were assessed using Cox proportional hazards models, and restricted cubic spline (RCS) analysis. Subgroup analyses and temporal lipid trajectories were also performed.ResultsOver a median follow-up of 13.8 years, 1,207 participants developed DLBCL. Lower levels of ApoA, HDL, and TC were significantly associated with increased DLBCL risk. RCS analysis revealed non-linear associations for ApoA and HDL, and a linear association for TC (P for non-linearity: 0.048, 0.017, and 0.139, respectively). Subgroup analysis indicated a significant interaction with age. Temporal trajectory analysis showed a gradual decline in ApoA and HDL levels during the 10 years prior to diagnosis, with a steeper drop in the last 5 years.ConclusionReduced levels of ApoA, HDL, and TC are linked to a higher risk of DLBCL. Notably, lipid changes precede clinical diagnosis by several years, suggesting their potential as early indicators for DLBCL risk stratification and preventive strategies.